ISOLASI DAN UJI ANTI JAMUR MINYAK ATSIRI KULIT KAYU SINTOK (Cinnamomum sintoc BL) PADA BEBERAPA JAMUR PERUSAK KAYU Isolation and Antifungal Test of Sintok Bark Essential Oil (Cinnamomum Sintoc BL) On Several Wood-Destroying Fungi - Nuwa Nuwa; Renhart Jemi; Herwin Joni (Agrienvi: Jurnal Ilmu Pertanian, 2018)
Essential oils are volatile compounds that are not soluble in water and are derived from aromatic plants. Some types of wood have the potential to contain essential oils, one of which is Sintok wood (Cinnamomum sintoc BLUME), which is included in the genus Cinnamomum from family Lauraceae. This study aims to determine the properties of essential oils of sintok bark and anti-fungal activity. The method of extracting essential oil by boiling Sintok bark obtained around the village of Hampangen, Katingan Regency, Central Kalimantan Province. The essential oil distilled is sintok bark which is fresh and the skin is dry air condition. Sintok wood essential oil was tested for the antifungal activity of Schizophyllum commune and Pleurotus osteratus. The yield of essential oils on fresh skin is 0.17% and dry air skin is 0.18%. Sintok wood essential oil with a concentration of 50 ppm can inhibit the growth of S.commune mushrooms and P. osteratus